(untitled) - Klaus, Carl H. (New York, 1968)
This collection is based on one very simple conviction - that the best way to develop a mastery of prose style is to immerse oneself in the prose of the best stylist and to read what they have written about style.
Keywords: English essays,Văn xuôi tiếng Anh,English prose literature,Bài luận tiếng Anh